Effect of acid modification on dyeing properties of Rajshahi silk fabric with different dye classes - Sheikh, M.R.K.; Farouqui, A.N.; Yahya, R.; Hassan, A. (2011)
In this paper, Rajshahi silk fabric was modified by acetic acid, tannic acid and their mixture. After acid modification, the silk fabric was dyed with three dyes classes namely: Reactive Orange 14, Direct Yellow 29 and Mordant Blue 9. Results revealed that the fabric modified with acid mixture of 30 acetic acid and 20 tannic acid improved the colorfastness of the dyed fabric after 7 days exposure on simulated sunlight and washing with hot soap solution. Also, the acid modification could improve the dyed fabrics' colorfastness properties to acids and alkalis. Optimum dyeing condition was observed at 1.5, 2.0, and 2.0 dyes for Reactive Orange 14, Direct Yellow 29 and Mordant Blue 9 respectively. The optimum dyeing time was observed 50, 60, and 50 min; and temperature was 90, 100 and 80 Â°C respectively. Modification of silk fabrics with acids improves the dyeability and colorfastness of Rajshahi silk fabrics. However, the acid modification could reduce the loss in tenacity of silk fabric upon exposure to sunlight.